Proceedings of the 45th Annual Design Automation Conference 2008
DOI: 10.1145/1391469.1391541
|View full text |Cite
|
Sign up to set email alerts
|

A progressive-ILP based routing algorithm for cross-referencing biochips

Abstract: Due to recent advances in microfluidics technology, digital microfluidic biochips and their associated CAD problems have gained much attention, most of which has been devoted to direct-addressing biochips. In this paper, we solve the droplet routing problem under the more scalable crossreferencing biochip paradigm, which uses row/column addressing scheme to activate electrodes. We propose the first droplet routing algorithm that directly solves the problem of routing in cross-referencing biochips. The main cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 7 publications
0
25
0
Order By: Relevance
“…Another more promising method is called cross-referencing, which applies high and low voltages to a row (column) and a column (row) electrode so as to activate the cell at the corresponding intersection point. Figure 1(b) gives an illustration of a cross-referencing biochip [6].…”
Section: Cross-referencing Dmfbmentioning
confidence: 99%
See 2 more Smart Citations
“…Another more promising method is called cross-referencing, which applies high and low voltages to a row (column) and a column (row) electrode so as to activate the cell at the corresponding intersection point. Figure 1(b) gives an illustration of a cross-referencing biochip [6].…”
Section: Cross-referencing Dmfbmentioning
confidence: 99%
“…Nevertheless, one can maximize the parallelism by carefully arranging voltages, and achieves routing result as good as routing in direct-addressing DMFB. In paper [6] and [7] it is shown that all the benchmarks can be routed by both proposed cross-referencing router. These routers are designed dedicatedly for routing in cross-referencing biochip.…”
Section: Electrode Interferencementioning
confidence: 99%
See 1 more Smart Citation
“…Su and Chakrabarty [16] have proposed an integer linear programming (ILP) model for scheduling and binding, considering a given allocation, but without addressing placement and routing. During the physical-level synthesis, the placement [18,25] of each module on the microfluidic array and the droplets routes [6,23,28] have to be determined.…”
Section: Related Workmentioning
confidence: 99%
“…Two approaches have been considered for solving this problem. The first approach, used in [17,23], consists in having a one-cell distance between any two adjacent modules, which is sufficient for isolating the functional regions on which operations are executing. However, if routing is not considered at the same time with placement, the resulted solution will require significant modifications for accomodating the necessary routes.…”
Section: Allocation and Placementmentioning
confidence: 99%